Do structural choice theory and the ‘risky lifestyles’ perspectives predict immunity as well as victimization? A test using zero-inflated mixed-effect SEM analyses of adolescent victimizations in South Korea - Rorie, Melissa (International review of victimology, 2022)
Adolescent victimization experiences can cause serious distress to victims and have been shown to be international phenomena. While victimization in various forms tends to peak in adolescence, its trajectories vary depending on individual and structural characteristics as well as the type of offending. Using structural choice theory and the ‘risky lifestyles’ perspective as our framework, the present study expanded on prior research by examining adolescent victimization in South Korea and using sophisticated statistical models to examine the unique predictors of ‘immunity’ in addition to victimization. In doing so, we supported previous research indicating that structural choice theory predicts adolescent victimization, but we added to that literature in finding that immunity was also a function of one’s environment as well as individual-level characteristics.